2022
DOI: 10.1007/s11663-022-02524-3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of CO2 in the Oxidation-Protection of Mg-Containing Aluminum Alloys

Abstract: TEM EDS–EELS and XPS have been performed on disc samples of Al alloys 5182 (AlMg4.5Mn0.4) and 6016 (AlSi1.2Mg0.4) heat treated in an oxidizing atmosphere of 76 pct synthetic air, 20 pct Ar, and 4 pct CO2. For both alloys, an amorphous C–C bonded layer on top of a nanocrystalline MgO layer was observed, which is believed to inhibit further oxidation of Mg for the 5182 alloy and breakaway oxidation for the 6016 alloy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…However, in some cases, prolonged exposure to elevated temperatures during the process can result in undesirable oxidation of the alloy. One major challenge in the development of aluminum alloys is the occurrence of oxidation during the solution heat treatment 9 . In previous experiments in our laboratory, it was shown that the addition of magnesium to the alloy had been identified as a major cause of oxidation during the treatment, which can lead to undesirable changes in the properties of the alloy.…”
Section: Introductionmentioning
confidence: 99%
“…However, in some cases, prolonged exposure to elevated temperatures during the process can result in undesirable oxidation of the alloy. One major challenge in the development of aluminum alloys is the occurrence of oxidation during the solution heat treatment 9 . In previous experiments in our laboratory, it was shown that the addition of magnesium to the alloy had been identified as a major cause of oxidation during the treatment, which can lead to undesirable changes in the properties of the alloy.…”
Section: Introductionmentioning
confidence: 99%